Tacit collusion: The neglected experimental evidence - Christoph Engel (Max Planck Institute for Research on Collective Goods, 2015)
Both in the US and in Europe, antitrust authorities prohibit merger not only if the merged entity, in and of itself, is no longer sufficiently controlled by competition. The authorities also intervene if, post merger, the market structure has changed such that "tacit collusion" or "coordinated effects" become disturbingly more likely. It seems that antitrust neglects the fact that, for more than 50 years, economists have been doing experiments on this very question. Almost any conceivable determinant of higher or lower collusion has been tested. This paper standardises the evidence by way of a meta-study, and relates experimental findings as closely as possible to antitrust doctrine.
Keywords: D43; K21; L13; L41; C91; D22; 330